Effective prices' as a device to analyze the impact of the Agenda 2000 and Mid-Term Review policy reforms on dairy and beef: measurement and simulation results for Germany - Roelof A. Jongeneel (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
The Agenda 2000 and the Mid-Term Review introduced a complex combination of policy changes for beef and dairy. It is not clear to what extent the package will influence production decisions. This study proposes a simple method for incorporating the effect of direct payments into the analysis of cow herd response. Effective support prices are derived by adjusting the Agenda 2000 reductions in dairy and beef support prices to reflect the compensation given to farmers in terms of direct payments and premiums. Following the Mid-Term Review different assumptions are made with respect to the extent to which these payments are, or are perceived as being coupled to production. The effective prices obtained for Germany are used in a simulation model to assess the impact of the latest agricultural policy reforms on German milk and beef producers.
Keywords: 330; Rinderhaltung; Milchviehhaltung; EU-Agrarpolitik; Agrarreform; Agrarsubvention; Deutschland